Penerapan Metode Hungarian Dalam Optimalisasi Penugasan Karyawan Sebagai Upaya Peningkatan Kualitas Pelayanan Pada Tirtamulya Cafe' - Frelydia Legianadirao; Feni Shafra Zahro; Hana Ropipah; Somadi Somadi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Tirtamulya Cafe is a Micro, Small, and Medium Enterprise (MSME) operating in the food and beverage sector. Currently, the allocation of employee tasks at the cafe does not align with individual capabilities, resulting in inefficient service processes and customer complaints. This study aims to determine the most effective task assignment by applying a descriptive quantitative approach using the Hungarian Method. Data were collected through observation and interviews. The results indicate a minimum total time of 13 minutes, with the following task allocation: Ananta as a waiter (7 minutes), Reva at the bar (3 minutes), and Reza as the cashier (3 minutes). These findings demonstrate that the method enables more accurate job placement, thereby enhancing service efficiency and supporting Tirtamulya Cafe's operational performance.